Plasma spray material containing YOF compound, its manufacturing method and thermal spray coating manufactured by the same
The Y-O-F coating layer with controlled molar ratios and atmospheric plasma jet spraying addresses porosity and hardness issues, enhancing stability and resistance to plasma gas interactions in semiconductor processes.
Patent Information
- Application Number
- JP2023104547
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-06-24
- Filing Date
- 2023-06-26
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2043-06-26
AI Technical Summary
Conventional Y-O-F plasma-soluble coating layers exhibit high porosity rates, low hardness, and susceptibility to physical ionic collisions, leading to particle generation and increased etching speed in semiconductor processes.
A method involving the use of a specific composition of Y-O-F compounds with controlled molar ratios and a manufacturing process using atmospheric plasma jet spraying to produce a coating layer with reduced porosity and enhanced hardness.
The resulting coating layer demonstrates improved physical and chemical stability, with reduced porosity and increased hardness, effectively resisting plasma gas interactions and minimizing particle generation during etching processes.
Smart Images

Figure 0007623428000010 
Figure 0007623428000011 
Figure 0007623428000012
Abstract
Description
[Technical field]
[0001] The present invention relates to a plasma spray material containing a YOF compound and a method for producing the same, and more particularly to a plasma spray material for plasma spray coatings having high plasma resistance and a method for producing the same. [Background technology]
[0002] In recent years, high integration and ultra-fine line width technology in semiconductor processes require plasma etching processes under ultra-extreme environments such as high density plasma, high cleanliness, and excessive electrical shocks. In particular, plasma etching processes using reactive gases containing halogen elements such as F, Cl, or Br, which have strong chemical reactivity, etch various deposition materials on the wafer surface, while at the same time causing damage to the component surfaces and generating non-volatile contaminant particles due to chemical and physical reactions with metal or ceramic components inside the chamber.
[0003] Therefore, there has been a great deal of interest in coating ceramic materials that exhibit excellent plasma resistance on the surfaces of metal or ceramic parts. 2 O 3 ) coatings are widely applied.
[0004] Yttrium oxide (Y 2 O 3 ) exhibits a high melting point (2,450°C), chemical stability, and crystallographic stability up to 2,300°C. 2 O 3 It has excellent chemical stability against F radicals, high resistance to ion bombardment due to the high atomic mass of yttrium, and the reaction product YF 3 It exhibits excellent plasma resistance due to its excellent mechanical properties.
[0005] However, the Y 2 O 3 At the beginning of the etching process on the upper surface of the coating layer, SF 6 , C.F. 4 , CHF3 When reacting with plasma gas such as HF, the concentration of fluorine gas in the chamber changes, increasing the seasoning time of the etching process. 2 O 3 The surface of the Y reacts with the plasma gas to form fluoro-containing contaminant particles. 2 O 3 When the device is subjected to thermal cycling, the contamination particles and Y 2 O 3 The difference in thermal expansion coefficient between the substrate and the substrate causes stress, which can cause contaminant particles to fall off.
[0006] To solve this problem, we used YF, which has excellent corrosion resistance. 3 However, the YF 3 During the Atmospheric Plasma Spraying (APS) process, the fluoride melts in the ultra-high temperature plasma, and some of the fluoride is oxidized, resulting in a coating layer that is partially mixed with fluoride and oxide. 2 O 3 Compared to thermal spray coating layers, this can lead to problems such as cracks in the coating layer and more particles being generated in the etching chamber.
[0007] Such a Y 2 O 3 and Y.F. 3 To solve the problem, 2 O 3 and Y.F. 3 A YOF coating layer with intermediate properties was introduced.
[0008] For example, Korean Patent Publication No. 10-2019-0017333 (Publication date: 2019.02.20.) discloses yttrium oxide (Y 2 O 3 ) powder and YF 3 The present invention discloses a method for producing YOF-based powders that can be used for coating semiconductor equipment by mixing the powders in a weight ratio of 1:2 to 2:1 and then heat treating them, which results in less generation of contaminating particles and excellent plasma resistance.
[0009] As another example, Korean Patent Publication No. 10-2019-0082119 (publication date: 2019.07.09) discloses that a YOF coating film is formed on a substrate using a mixed powder containing Y, O, and F, and that by making the composition of the Y:O:F by XPS 1:1:1, the porosity is reduced to 0.01-1.0% and the hardness is improved to 6-12 GPa, and a coating film having high etching resistance against corrosive gases and high-speed colliding ion particles and excellent plasma resistance can be provided. [Prior art documents] [Patent documents]
[0010] [Patent Document 1] KR2019-0017333A [Patent Document 2] KR2019-0082119A [Patent Document 3] JP6918996B [Patent Document 4] JP7035293B Summary of the Invention [Problem to be solved by the invention]
[0011] The above-mentioned conventional YOF plasma spray coating layer has the following problems. First, the conventional YOF plasma spray coating layer has a significantly higher porosity than plasma spray coating layers made of other ceramic materials. 2 O 3 , Y.F. 3While the coating layer shows a good porosity of within 3%, the YOF coating layer shows a high porosity of over 7%. Particle size is one of the factors that affect porosity, and the smaller the particle size, the lower the porosity and surface roughness of the coating layer tends to be. However, for particles below a certain size, there is a technical problem that as the size decreases, the cohesive force increases due to the narrower interparticle distance, and frictional static electricity generated during powder transport makes it impossible to transport the powder to the plasma center, so there is a limit to how much porosity can be reduced by reducing the particle size.
[0012] Secondly, the hardness of the YAG plasma spray coating layer is lower than that of plasma spray coating layers made of other ceramic materials. 2 O 3 The coating layer exhibits a hardness of 450 to 550 Hv, while the YOF coating layer exhibits a hardness of 300 to 400 Hv. Even if the YOF coating layer is chemically stable, it is easily etched by physical ion bombardment that occurs during the dry etching process due to its low physical properties, and the generation of particles can be a fatal flaw in the coating layer, and the weak mechanical properties can also be a problem in the manufacturing process of the thermal spray coating layer.
[0013] Finally, YOF plasma spray coating layers are known to be robust in processes that use oxygen radicals and fluorine-based plasma gases simultaneously. However, in some processes, the high fluorine content can lead to the formation of F during the process. - There is a problem in that the ion gas is mixed into the semiconductor process, increasing the etching rate.
[0014] Therefore, the present invention aims to provide a YOF coating layer that has a lower porosity and higher hardness than conventional YOF plasma spray coating layers while having a ternary compound as a main component, and has physical and chemical stability against plasma gas generated in an etching process.
[0015] Another object of the present invention is to provide a thermal spray material suitable for producing a YOF plasma spray coating layer having improved properties.
[0016] Another object of the present invention is to provide a method for producing the above-mentioned thermal spray material. [Means for solving the problem]
[0017] In order to achieve the above technical objectives, the present invention provides a material for plasma spraying containing an yttrium compound, in which the molar numbers of Y, O, and F in the yttrium compound satisfy 1.5<(O+F) / Y<2.0.
[0018] In the present invention, the yttrium compound is a YOF compound and Y 2 O 3 In this case, the YOF compound may include a first YOF compound having O / F=1 and a second YOF compound having O / F<1. The second YOF compound may include Y 4 O 3 F 6 , Y 5 O 4 F 7 , Y 6 O 5 F 8 and Y 7 O 6 O 9 and exemplarily, the second YOF compound may comprise at least one compound selected from the group consisting of Y 5 O 4 F 7 may include:
[0019] In the present invention, the content of the second YOF compound is preferably lower than the content of the first YOF compound.
[0020] In the present invention, Y in the material for plasma spraying 2 O 3 The content is preferably 10 to 30%, and more preferably 15 to 25%.
[0021] In order to achieve the above-mentioned other technical object, the present invention provides a method for producing a material for plasma spraying, comprising: (a) a step of feeding an yttrium compound powder into an atmospheric plasma jet to melt the powder; and (b) a step of cooling the molten yttrium compound droplets to produce an yttrium compound powder.
[0022] In the present invention, the above step (b) may include: (b1) a step of injecting the molten yttrium compound droplets into a refrigerant; and (b1) a step of removing the refrigerant and drying after the step (b1).
[0023] When the molten droplets are sprayed in the step (b1), the separation distance from the spray outlet to the surface of the refrigerant is preferably 400 to 600 mm.
[0024] In the present invention, in the yttrium compound powder in step (b), the mole numbers of Y, O and F preferably satisfy 1.5<(O+F) / Y<2.0.
[0025] In order to achieve still another technical object described above, the present invention provides a plasma spray coating, which is characterized in that, in a material for plasma spraying containing an yttrium compound, the molar numbers of Y, O, and F in the yttrium compound satisfy 1.6<(O+F) / Y<1.9 and the porosity is 3% or less. Effect of the Invention
[0026] According to the present invention, it is possible to provide a YOF thermal spray coating layer having low porosity and high hardness, and having physical and chemical stability against plasma gas generated in the etching process.
[0027] In addition, according to the present invention, by spheroidizing the YOF-based powder by air melting, it is possible to provide a YOF-based thermal spray material having a dense structure and high density as well as a high O / F ratio in a simple manner. [Brief description of the drawings]
[0028] [Figure 1] 1 is a diagram showing a schematic diagram of a method and an apparatus for producing a thermal spray material according to one embodiment of the present invention. FIG. [Diagram 2] 6 is a photograph showing the appearance of powder before and after plasma treatment in one embodiment of the present invention. [Diagram 3] 1 is a graph showing the results of XRD analysis of powder before and after plasma treatment in one embodiment of the present invention. [Figure 4] 1 is an electron microscope photograph of a cross section of a thermal spray powder produced according to an embodiment of the present invention. [Diagram 5] 1 is an electron microscope photograph of a cross section of a thermal spray coating produced according to an embodiment of the present invention. [Figure 6] 1 is a graph showing the results of XRD analysis of a thermal spray coating produced according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0029] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs. Generally, the nomenclature used herein is one that is well known and commonly used in the art.
[0030] Throughout this specification, when a part "comprises" an element, this does not mean that it excludes other elements, but that it may further include other elements, unless otherwise specified.
[0031] Furthermore, throughout this specification, the term "non-spheronized" refers to a state that has not undergone the spheronization process described in the present invention.
[0032] In the present specification, YOF compounds are defined as compounds containing the chemical element Y x O y F z However, it is not limited thereto, and may contain a small amount of additional elements that can be dissolved while maintaining the crystal structure.
[0033] In the present invention, the YOF compound is, for example, YOF, Y 7 O 6 F 9 , Y 6 O 5 F 8 , Y 5 O 4 F 7 , and Y 4 O 3 F 6 The compounds known as YOF compounds having a molar ratio of O / F of 1 are YOF, and the remaining compounds have an O / F of less than 1. x O y F z In the case of a YOF compound expressed by the formula: the smaller the x, the smaller the O / F molar ratio becomes, and the more F-rich the compound becomes.
[0034] The plasma spray material of the present invention contains at least two different YOF compounds. In the present invention, the first YOF compound is YOF and the second YOF compound is Y 7 O 6 F 9 , Y 6 O 5 F 8 , Y5 O 4 F 7 and Y 4 O 3 F 6 The compound may be at least one compound selected from the group consisting of:
[0035] The O / F molar ratio and (O+F) / Y molar ratio of each YOF compound mentioned in the present specification are expressed as Y 2 O 3 and Y.F. 3 In comparison, the situation is as shown in Table 1 below.
[0036] [Table 1]
[0037] As described above, the plasma spray material of the present invention is a YOF having a (O+F) / Y ratio of 2 and a YOF compound having a (O+F) / Y ratio of more than 2, such as Y 7 O 6 F 9 , Y 6 O 5 F 8 , Y 5 O 4 F 7 , and Y 4 O 3 F 6 Even in this case, the plasma spray material of the present invention has a value of (O+F) / Y in the entire composition of less than 2.0.
[0038] Preferably, (O+F) / Y in the total composition may be 1.99, 1.98, 1.97, 1.96, or 1.95 or less. Also, (O+F) / Y in the total composition of the plasma spray material of the present invention may be 1.8 or more, 1.85 or more, or 1.9 or more.
[0039] In the composition of the plasma spray material of the present invention, Y 2 O 3 The content of Y in the composition may be 10% by weight or more, or 15% by weight or more. 2 O3 The content may be 30% by weight or less, or 25% by weight or less.
[0040] As described above, in the present invention, the material for plasma spraying is a first YOF compound consisting of YOF and Y 7 O 6 F 9 , Y 6 O 5 F 8 , Y 5 O 4 F 7 and Y 4 O 3 F 6 In this case, the content (wt %) of the first YOF compound is preferably greater than the content of the second YOF compound.
[0041] According to another aspect of the present invention, the above-mentioned plasma spray material of the present invention may be produced by including the steps of (a) feeding a powder containing an yttrium compound into a plasma jet and melting the powder, and (b) cooling the molten powder droplets.
[0042] 1 is a schematic diagram showing a method and apparatus for producing a thermal spray material according to one embodiment of the present invention. The production process of the present invention will be described below with reference to this diagram.
[0043] In the present invention, step (a) is a step of feeding a powder of an yttrium compound composition into an atmospheric plasma jet and melting it.
[0044] When generating thermal plasma in a plasma device, arc discharge is generated between the cathode and both electrodes while a large amount of gas is flowing, and plasma is blown out in a jet state. This is called a plasma jet or plasma torch, and in the step (a), powder is put into the plasma jet and melted in a short time. In this case, in the present invention, when the plasma device generates the plasma jet in a state where it is open to the atmosphere, this is called an atmospheric plasma jet.
[0045] In the present invention, (O+F) / Y in the powder composition fed into the plasma jet may be 2.1 or more, 2.2 or more, 2.3 or more, 2.4 or more, or 2.5 or more, and may be 3.0 or less, 2.9 or less, 2.8 or less, 2.7 or less, or 2.6 or less.
[0046] Illustratively, the powder composition comprises a YOF compound, e.g., YOF, Y 7 O 6 F 9 , Y 6 O 5 F 8 , Y 5 O 4 F 7 , and Y 4 O 3 F 6 The powder composition may contain at least one compound selected from the group consisting of YF 3 It may further include.
[0047] In the present invention, the plasma device is one that has a temperature sufficient to melt the powder, and is preferably an Atmospheric Plasma Spraying (APS) device.
[0048] Next, the step (b) is a step of cooling the molten droplets. This step is performed by cooling the molten droplets with water, N 2 The molten YOF-based droplets may be rapidly sprayed into a refrigerant using one or more of the following:
[0049] Specifically, the separation distance means the distance from the spray nozzle of a plasma spray gun to the surface of the refrigerant, and is preferably kept in the range of 300 to 800 mm so that the molten YOF-based droplets can be sprayed into the refrigerant without loss and a quenching effect can be achieved while improving the yield. More preferably, the separation distance is kept in the range of 400 to 600 mm. If the separation distance is less than 400 mm, the solvent and powder losses due to the spray pressure become considerable, and if it exceeds 600 mm, the yield decreases due to the spray angle, and it is difficult to achieve a sufficient quenching effect for the molten powder.
[0050] The refrigerant rapidly cools the molten yttrium compound droplets that are sprayed, making them spherical and densifying them. Specifically, the molten droplets that are rapidly sprayed into the refrigerant are rapidly cooled and quenched, so that the droplets are formed into a spherical shape to minimize surface energy and are densified, thereby improving hardness. The refrigerant may be water, N 2 and Ar, and the component ratio of the produced powder can be adjusted by the refrigerant.
[0051] As an example, a molten droplet is placed in distilled water (H 2 When yttrium compounds are rapidly sprayed into distilled water and quenched by rapid cooling, the F content of the compounds decreases by reacting with the hydrogen in the distilled water to form hydrogen fluoride. 2 When argon or argon is used as the refrigerant, the mixture is quenched without reacting with the yttrium compound, and the F content is not reduced. In this way, the composition of the powder produced can be adjusted by adjusting the refrigerant.
[0052] After cooling of the droplets, the refrigerant is removed and the resulting powder can be dried as appropriate. The steps of removing the refrigerant and drying the powder can be carried out by conventional methods, the details of which will not be described here.
[0053] The powder produced by this method is a spherical powder with a particle size of 10 to 60 μm. Generally, the smaller the diameter of the YOF-based particles, the denser the coating layer can be formed. However, if the diameter of the particles is less than 10 μm, the narrow interparticle distance generates cohesion, which may cause a technical problem of feeding failure. Therefore, the spherical powder of the present invention has a particle size of 10 μm or more, so that the density is increased while the particles are not cohesed during coating, allowing high-density coating to be formed, and preferably the average particle size of the molten powder is 15 to 45 μm.
[0054] In the present invention, the thermal spray material produced by melting and quenching in the plasma jet has properties different from those of the raw material powder fed into the plasma device.
[0055] First, the thermal spray material produced in the present invention is a spherical powder having a hollow interior and a dense shell on the outside, and the outer diameter of the powder shrinks due to densification.
[0056] Next, the yttrium compound produced by the production method of the present invention has a variation in anion composition compared to the raw material powder. For example, according to the present invention, when the yttrium compound is expressed as YX (wherein X is an anion and is oxygen and / or fluorine), the molar ratio of anion (X) to cation (Y) in the compound, i.e., X / Y, varies based on 2. Illustratively, the yttrium compound of the raw material powder has a value of 2 or more, but the X / Y of the thermal spray material treated with the atmospheric plasma jet shifts to a value lower than 2. This is understood to be because the air in the atmosphere is mixed into the plasma jet flame by the plasma treatment in an atmospheric pressure atmosphere and reacts with the droplets in the plasma jet.
[0057] As described above, a material for plasma spraying produced by treating a raw material powder in an atmospheric plasma jet for a short period of time can have the following characteristics.
[0058] First, the increase in oxygen content in the plasma spray material can result in an oxygen-rich yttrium compound compared to the powder before plasma treatment. Second, the plasma spray material can be treated for a short treatment time, allowing yttrium compounds with X / Y>2 and yttrium compounds with X / Y<2 to exist in a mixed state. Furthermore, the plasma spray material of the present invention can produce dense spherical powder by melting.
[0059] A method for producing a thermal spray coating using the thermal spray material described above in the present invention will be described below.
[0060] Atmospheric Plasma Spray (APS) is a thermal spray technology that converts powder or linear materials from a high-temperature heat source into molten droplets, which are then collided with a substrate at high speed to rapidly cool and solidify, forming a layered coating. More specifically, APS uses Ar, He, N 2 This is a coating formation technology in which gases such as those mentioned above are turned into plasma by an arc and then discharged from a nozzle to create an ultra-high temperature, high-velocity plasma jet as a heat source. The spray material collides with the workpiece at high speed, which has the advantage of making it possible to produce a coating with high adhesion strength and high density. However, because the process is carried out in an atmosphere at atmospheric pressure, surrounding air can get mixed into the plasma jet flame, resulting in a coating with high porosity and, depending on the coating material, containing oxides or impurities.
[0061] The yttrium compound coating layer produced by coating the thermal spray material produced by the above-mentioned method on a substrate using the APS method is dense with a porosity of less than 2% and exhibits high hardness of 550 Hv or more. In addition, since the mechanical properties are significantly improved, the resistance to physical ion bombardment occurring in the dry etching process can be increased.
[0062] The increase in resistance to ion bombardment is due to a change in the molar ratio of (O+F) / Y in the yttrium compound forming the coating layer. This is because the oxygen content in the yttrium compound increases due to oxidation that occurs during the spheroidization process of the thermal spray material and additional oxidation that occurs during coating with the APS. As a result, the thermal spray coating contains yttrium compounds with an O / F ratio of less than 1, such as Y 7 O 6 F 9 , Y 6 O 5 F 8 , Y 5 O 4 F 7 , or Y 4 O 3 F 6 Preferably, the YOF compound present in the thermal spray coating of the present invention is a YOF having an O / F of 1.
[0063] The (O+F) / Y ratio of the yttrium compound coating formed by the above-mentioned atmospheric plasma spraying may be less than 1.9, less than 1.85, less than 1.8, or less than 1.75, and may be greater than 1.6, greater than 1.65, or greater than 1.7. Preferably, the thermal spray coating of the present invention contains YOF and Y as the yttrium compound. 2 O 3 Contains Y 2 O 3 The content (wt%) of Y in the coating is greater than the content of YOF. 2 O 3 The content (wt%) of is preferably at least twice the content of YOF.
[0064] Furthermore, the yttrium compound coating produced by the present invention is a dense thermal spray coating having a porosity of 3% or less, more preferably 2% or less.
[0065] The present invention will be described in more detail below by way of examples, but the present invention is not limited to these examples.
[0066] A. Manufacturing of yttrium compound thermal spray materials Granular powder of an yttrium compound having the composition shown in Table 2 below was subjected to atmospheric plasma spraying treatment using the plasma spraying apparatus shown in FIG.
[0067] [Table 2]
[0068] After forming plasma in the apparatus of FIG. 1, yttrium compound powder having the composition shown in Table 2 was injected into the plasma flow and heated. At this time, the plasma formation conditions, powder injection angle, and other conditions were as shown in Table 3 below. In addition, the separation distance between the nozzle of the plasma gun and the cooling medium surface was maintained at 300 to 800 mm. After the ejected droplets were quenched by contacting with water, the spherical powder was separated from the water and dried. Powder injection can be performed in a single feeder or double feeder manner, and the powder injection angle was set to 90° in the single feeder, and 90° on one side and 105° on the other side in the double feeder.
[0069] [Table 3]
[0070] The yield of the thermal spray coating depending on the separation distance was calculated by the following formula.
[0071] Yield (%) = (total amount of powder obtained after drying / total amount of powder added) * 100
[0072] Table 4 shows the yield by isolation distance.
[0073] [Table 4]
[0074] From Table 4, it can be seen that the highest yield is obtained at 400 to 600 mm.
[0075] Figure 2 (a) and (b) are photographs showing the appearance of the granular raw material powder used in this experiment and the thermal spray material obtained after plasma treatment, respectively.
[0076] Fig. 2(b) shows the appearance of the spherical powder densified by melting after plasma treatment, while Fig. 4 shows a cross section of the thermal spray powder produced by the present invention, which shows that the thermal spray powder particles have a hollow interior and a densified shell structure on the periphery.
[0077] On the other hand, the granular raw material powder particles on the left have a size of approximately 30 μm, while the molten particles on the right have a size of 20 μm or less, indicating that the particle size is significantly reduced.
[0078] FIG. 3 is a graph showing the results of X-ray diffraction (XRD) analysis of the granular raw material powder used in this experiment and the thermal spray material powder obtained after plasma treatment.
[0079] As shown in the figure, the granular raw material powder is Y 5 O 4 F 7 and Y.F. 3 However, the plasma-treated thermal spray powder has a prominent YOF peak and Y 2 O 3 While the peak is observed, Y 5 O 4 F 7 The peak decreased, and YF 3 The peaks are essentially undetectable.
[0080] Table 5 below shows the results of quantitative XRD analysis of the granular raw material powder and the thermal spray powder. Table 5 shows the (O+F) / Y molar ratio calculated from the quantitative analysis results.
[0081] [Table 5]
[0082] B. Plasma spray coating production A thermal spray coating was produced by air plasma spraying (APS) using the thermal spray powder produced in the above experimental example (Example). At this time, Al 6061 (50mm x 50mm x 5T) was used as the substrate. For comparison, a thermal spray coating was produced by APS using the granular raw material powder used in the above experimental example (Comparative Example).
[0083] The plasma spraying conditions for producing the thermal sprayed coatings of the examples and comparative examples are summarized in Table 6 below.
[0084] [Table 6]
[0085] The hardness, porosity, and surface roughness of the produced thermal spray coating were measured. The porosity was calculated as the ratio of the area of the pores in the cross-sectional photograph of the thermal spray coating taken with a scanning electron microscope (SEM) using the image analysis software Image Pro.
[0086] The etch rate of the thermal spray coating was measured. The thermal spray coating was etched using Lam Kiyo 45 equipment under the etching conditions shown in Table 7 below, and the etch rate was calculated by measuring the step difference at the boundary between the etched area and the non-etched area using an AFM.
[0087] [Table 7]
[0088] 5(a) and (b) are electron microscope photographs of the cross sections of the thermal spray coatings produced in the comparative example and the example, respectively.
[0089] Referring to FIG. 5, it can be seen that the thermal sprayed coating of the example is a much denser coating than the thermal sprayed coating of the comparative example.
[0090] FIG. 6 is a graph showing the results of X-ray diffraction analysis of the thermal spray coatings produced in the comparative example and the example, respectively.
[0091] Referring to FIG. 6, the thermal spray coating of the embodiment has a high Y 2 O 3 It can be seen that the YOF compound that was present in the thermal spray material is no longer present, which indicates that the F content in the thermal spray coating composition has decreased and the oxygen content has increased.
[0092] Table 8 below shows the results of quantitative XRD analysis of the thermal spray coatings of the comparative examples and examples. Table 8 shows the (O+F) / Y molar ratios calculated from the quantitative analysis results.
[0093] [Table 8]
[0094] Table 9 below summarizes the measurement results of the hardness, porosity, surface roughness and etching rate of the thermal spray coating.
[0095] [Table 9]
[0096] From Table 9, it can be seen that the thermal sprayed coatings of the examples have a dense structure and have high hardness and high resistance to etching.
[0097] Although the present invention has been described above with reference to exemplary embodiments and drawings, these are merely provided to aid in a more comprehensive understanding of the present invention, and the present invention is not limited to the above embodiments, and those skilled in the art will understand that various modifications and variations are possible without departing from the essential characteristics of the present invention. Therefore, the idea of the present invention should not be limited to the described embodiments, and any modifications within the scope of the claims, as well as those within the scope of the claims, should be interpreted as being included in the scope of the present invention. The present disclosure includes the following embodiments. <1> A plasma spray material comprising a yttrium compound, A material for plasma spraying, wherein the molar numbers of Y, O, and F in the yttrium compound satisfy 1.5<(O+F) / Y<2.0. <2> The yttrium compound is YOF compounds and Y 2 O 3 The method according to claim 1, <1> The plasma spray material according to claim 1. <3> The YOF compound is The method comprises the steps of: (a) providing a first YOF compound having O / F=1 and (b) providing a second YOF compound having O / F<1; <2> The plasma spray material according to claim 1. <4> The second YOF compound is Y 4 O 3 F 6 、Y 5 O 4 F 7 、Y 6 O 5 F 8 and Y 7 O 6 O 9 The above-mentioned comprises at least one compound selected from the group consisting of <3> The plasma spray material according to claim 1. <5> The second YOF compound is Y 5 O 4 F 7 The method according to claim 1, <3> The plasma spray material according to claim 1. <6> The content of the second YOF compound is lower than the content of the first YOF compound. <3> The plasma spray material according to claim 1. <7> The above Y2 O 3 The content is 10 to 30%. <2> The plasma spray material according to claim 1. <8> The above Y 2 O 3 The content is 15 to 25%. <2> The plasma spray material according to claim 1. <9> A plasma spray material comprising a yttrium compound, A plasma spray coating, characterized in that the molar numbers of Y, O and F in the yttrium compound satisfy 1.6<(O+F) / Y<1.9, and the porosity is 3% or less.
Claims
1. A plasma spray material containing an yttrium compound, the material being a spherical powder having a particle size of 10 to 60 μm, a hollow interior, and an exterior shell, The molar numbers of Y, O and F in the yttrium compound satisfy 1.5<(O+F) / Y<2.0, The yttrium compound is a Y—O—F compound and a Y 2 O 3 Including, The Y—O—F compound comprises a first Y—O—F compound in which O / F=1 and a second Y—O—F compound in which O / F<1.
2. The second Y—O—F compound is Y 4 O 3 F 6 , Y 5 O 4 F 7 , Y 6 O 5 F 8 and Y 7 O 6 O 9 2. The material for plasma spraying according to claim 1, comprising at least one compound selected from the group consisting of:
3. The second Y—O—F compound is Y 5 O 4 F 7 The plasma spray material of claim 1 , comprising:
4. 2. The material for plasma spraying according to claim 1, wherein the content of the second Y—O—F compound is lower than the content of the first Y—O—F compound.
5. The Y 2 O 3 2. The material for plasma spraying according to claim 1, wherein the content is 10 to 30%.
6. The Y 2 O 3 The material for plasma spraying according to claim 1, characterized in that the content is 15 to 25%.
7. A plasma spray coating comprising a yttrium compound, The molar numbers of Y, O, and F in the yttrium compound satisfy 1.6<(O+F) / Y<1.9, and the porosity is 3% or less; The yttrium compounds are YOF and Y 2 O 3 Including, Y in the membrane 2 O 3 The weight of the plasma sprayed coating is greater than the weight of the YOF.
Citation Information
Patent Citations
Material for spray coating, sprayed coating, and member with sprayed coating
JP2018076546A
Thermal spraying materials, thermal spray coatings, and thermal spray coated components
JP6918996B2
Film-forming materials
JP7035293B2
Manufacturing method of YOF based powder
KR1020190017333A
Forming method of coating film and coating film thereof
KR1020190082119A